STUDI EKSPERIMEN KINERJA SISTEM REFRIGERASI SETENGAH SIKLUS PADA KENDARAAN BERBAHAN BAKAR LPG - Prima Nofan Ryastama; Damar Setyo Prakasa; Muhammad Latifur Rochman; Muji Setiyo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
The Air Conditioning (AC) system is an important requirement for vehicle passengers to get thermal comfort. However, the AC system draws power from the engine to drive the compressor. Meanwhile, vehicles driven by Liquefied Petroleum Gas (LPG) provide decent cooling potential to assist the main air conditioning system. Therefore, this study aims to examine the effect of cooling on LPG-fueled vehicles by utilizing LPG flow to be used as a secondary refrigerant. The research was carried out on a 1495 cc engine with a special evaporator which was tested at variations of blower speed 1, 2, and 3. The tests were carried out at engine speeds of 1000, 2000, and 3000 rpm. The results showed the lowest cooling effect at blower speed level 1 with engine speed of 1000 rpm and the highest at blower speed level 3 with engine speed of 3000 rpm. The greatest cooling effect is obtained at 373 Watts at 3000 rpm engine speed and level 3 blower speed.